Peran MUI Pekanbaru Komisi Pembangunan Ekonomi Umat Dalam Mengembangkan Ekonomi Syariah Di Kota Pekanbaru - yona Fitri; Mohd. Fikri Azhari; Mariatul Fitri (Finest : Jurnal Riset dan Pengembangan Ekonomi Islam, 2021)
This writing is based on the problems where many people in Pekanbaru city still do not understand about Sharia economy. Where the city of Pekanbaru which most of the population is Muslim but there are still many people who do not understand what is Sharia economy. The data of this research were collected through interview technique, documentation and literature study. The types and sources of data used in this study are primary data obtained directly through interviews with members of the MUI Pekanbaru city and documentation with members of the MUI Pekanbaru.Sedangkan secondary data obtained from the journal MUI Pekanbaru city and with the literature associated with this research. The result of the research shows that the work program of MUI of Pekanbaru City is now available, but its role has not been seen because when doing research MUI Pekanbaru experience change of stewardship so that the work program has not been implemented yet. However, MUI Pekanbaru has plans to conduct workshop / training in next year. The role of Indonesian Ulema Council of Pekanbaru city is currently trying to empower small traders and students in the form of training. The Indonesian Ulema Council of Pekanbaru also runs its role through preaching to mosques. The influence of MUI of Pekanbaru on the development of Sharia economy, Economic Development Commission of Ummah always encourage people to apply Sharia economy in daily life, starting from saving in Syariah bank and shopping at sharia center like Sharia Supermarkets.